Rekonsiliasi Kristiani: Berpijak dari Pemikiran Robert J. Schreiter - Dadang, Andreas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
Reconciliation process is a process of truth unfolding and memory recovery. What is the center of attention in this recovery and disclosure process? Reconciliation seeks to uncover and restore the truth and justice of the narratives of the past. Through the reconciliation process, it is expected that what really happened and what has beenthe real wound of the victims can be recovered through the process of uncovering the truth. Robert J. Schreiter'sview about the reconciliation process includes three basic attempts, i.e., the truth telling, the pursuit of justice, and the healing of memories and forgiveness. Considering the long and complex process of reconciliation, he further develops the three stage process of reconciliation from the Christian perspective, which can be phrased as the genesis stage, the transformation stage, and the readjustment stage. This Christian reflection of reconciliation processgives rise to a spirituality of reconciliation that includes the attitude of listening and waiting, the focus on attention and concern, and the paradigm shift. The biblical basis of the spirituality of reconciliation is further explored in the light of Paul, the passion narratives, and the narratives of Jesus' appearance after the resurrection.